Studi Tentang Pembinaan Terhadap Narapidana di Lembaga Pemasyarakatan Kelas I Makassar - Asri Ainun Bakhtiar; Heri Tahir; Nurharsyah Khaer Hanafie; Najamuddin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of prisoners is an important aspect of the Correctional System which aims to improve the quality of personality and independence of prisoners so that they realize their mistakes, improve themselves, and not repeat criminal acts, so that they can be accepted back by the community. This study aims to analyze the “Pattern of Development of Prisoners at the Makassar Class I Correctional Institution”. The approach used in this research is a qualitative approach using a type of sociological juridical research with data sources obtained from Makassar Class I Correctional Institution Officers by the Community Guidance Section, Work Guidance Section and Registration Section and Prisoners at Lembaga Pemasyarakatan Kelas I Makassar. The pattern of coaching at at Lembaga Pemasyarakatan Kelas I Makassar is carried out in two forms in accordance with applicable regulations, namely personality development and independence development. However, the implementation of this coaching has not fully run optimally. In the implementation of coaching, Lembaga Pemasyarakatan Kelas I Makassar needs to provide different treatment between prisoners. Not all prisoners can be given the same approach, because their needs and conditions are different. Based on the data obtained, the dominant types of criminal offenses in Makassar Class I Correctional Institution include narcotics, child protection, corruption, murder and theft. Each of these categories has certain characteristics that require specific coaching approaches.